PENDAMPINGAN KUNJUNGAN KEPADA ANAK STUNTING DAN IBU HAMIL BERSAMA IBU BIDAN BESERTA KADER DESA PASEHKIDUL - Nuriyah Fauzia Zahra, Yeni Sulaeman, Masrupi, Rusmiyadi (JURNAL PENGABDIAN KEPADA MASYARAKAT SERUMPUN MENGABDI, 2024)
In 2024, the Sumedang Regency Government has submitted a program to LLDIKTI regarding empowerment for its community. Namely by sending the best students from all universities in West Java and Banten so that there will be a LLDIKTI Region IV THEMATIC KKN Program which will be held for 4 months from 17 February-17 June 2024 in Sumedang Regency, West Java Province.  Then, the Sumedang Government proposed 5 KPI achievements, namely: 1. New Zero Stunting, 2. Literacy for the extreme poor, 3. Social Welfare Center, 4. One Village One Product, and 5. One Village One Innovation. The most important program is launching a strategy to accelerate stunting reduction with a family approach through assisting families at risk of stunting in achieving the targets, namely prospective brides/prospective couples of childbearing age, pregnant and breastfeeding mothers until after giving birth and children aged 0-59 months. The majority of people do not understand stunting, and there is still an opinion that stunting is a hereditary factor. Community service activities are carried out in order to increase knowledge, understanding and community participation in efforts to prevent and early detect stunting. The method used is through home visits using community approaches, observation, interviews, outreach and mentoring. The results obtained are information on pregnant women respondents based on age, education and gravida, baby respondents based on age and gender. Observation activities obtained information about risk factors in pregnancy and childbirth, while socialization and mentoring activities were carried out actively and participated enthusiastically by respondents. The conclusions can increase the understanding of pregnant women and mothers regarding the meaning, causes, risks, symptoms, prevention of stunting, the importance of exclusive breastfeeding and the importance of Fe tablets to prevent anemia in pregnancy. This is an effective strategy to empower families to increase preparedness, especially in preventing stunting.